2017
DOI: 10.1016/j.brq.2016.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Related-party transactions, dominant owners and firm value

Abstract: We examine RPTs in one Continental European country, Spain, where ownership concentration is prevalent and state ownership is practically non-existent. Our results show that more than half of listed Spanish firms commit to RPTs over the analyzed period. Furthermore, from the perspective of the related party to the transaction, connected transactions between listed Spanish firms and their blockholders account for 99.84% of the total RPTs carried out by listed Spanish firms. Finally, our findings reveal that fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
59
2
13

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(78 citation statements)
references
References 98 publications
(320 reference statements)
4
59
2
13
Order By: Relevance
“…In this sense, firms in financial distress or with difficulties for financing new projects have a higher propensity to sell their accounts receivable (Sopranzeti, 1999). Moreover, business groups, which are more prominent in countries with lower investor protection, might also use a commercial transaction for engaging in tunneling activities by using related party transaction (Bona-Sánchez et al, 2017). From the practitioner’s perspective, firms usually have too much investment in NWC that can be transformed in cash for more efficient uses (Ek & Guerin, 2011; Ernst and Young, 2016).…”
Section: The Value Of Nwc Across the Worldmentioning
confidence: 99%
“…In this sense, firms in financial distress or with difficulties for financing new projects have a higher propensity to sell their accounts receivable (Sopranzeti, 1999). Moreover, business groups, which are more prominent in countries with lower investor protection, might also use a commercial transaction for engaging in tunneling activities by using related party transaction (Bona-Sánchez et al, 2017). From the practitioner’s perspective, firms usually have too much investment in NWC that can be transformed in cash for more efficient uses (Ek & Guerin, 2011; Ernst and Young, 2016).…”
Section: The Value Of Nwc Across the Worldmentioning
confidence: 99%
“…When this relationship becomes negative (share ownership more than 42.78%), the purpose of the domestic institutional shareholders is no longer to increase the firm value measured by Tobin Q, there may be other objective, such as related party transactions, as explained by Sánchez et. al (2017) [21].…”
Section: Resultsmentioning
confidence: 99%
“…Huang and Liu () documented that related‐party transactions cause more severe agency costs and thus bring about negative impacts on the corporate performance of Taiwanese high‐technology firms. Similarly, Bona‐Sánchez, Fernández‐Senra, and Pérez‐Alemán () concurred on the expropriation effect of related‐party transactions, and Wang, Cho, and Lin () also showed that related‐party transactions are negatively related to corporate performance. Since related‐party transactions could also be driven by transaction‐cost concerns, which leads to better firm performance., this study states the first hypothesis in its nondirectional form as follows.Hypothesis Related‐party transactions affect corporate performance.…”
Section: Prior Studies and Hypotheses Developmentmentioning
confidence: 87%